Gemeinsame Elternverantwortung - Eine rechtsvergleichende Studie zu Grundfragen und Problemen beim Elternkonflikt getrennt lebender Eltern - Mecke, Christoph-Eric (Universitätsverlag Göttingen, 2018)
In this volume, the law of parental responsibility in Europe is examined on a comparative basis for Belgium, Germany, England and Wales, the Netherlands, Poland and Sweden. This closes a gap in the research, as there is currently no such current study available. A presentation of the main features of the law of parental responsibility is followed by a comparative typification and analysis of the rules regarding the exercise of joint parental responsibility and the legal representation of the child in cases of parental separation; those rules are explored from the point of view of the tension between parental autonomy and enforced parental cooperation. The legal solutions to parental conflicts are a further focal point; this is dealt with in depth regarding parental conflicts over the child's place of residence and legal rules about alternating residence of the child in Australia, Belgium and Sweden. Volume 21 of the series "Göttinger Juristische Schriften" (Göttingen Legal Writings) The series is published by the Faculty of Law of the Georg-August-University and makes faculty activities accessible to an interested public.